P-464 Long-acting GnRH agonist ovulation trigger to avoid ovarian hyperstimulation and to combine oocyte cryopreservation with ovarian suppression during chemotherapy. (30th June 2022) - Massarotti, C; Gazzo, I; Stigliani, S; Lambertini, M; Sozzi, F; Scaruffi, P; Anserini, P
Abstract: Study question: Is long-acting GnRH agonist (GnRHa) trigger an efficacious and safe option in oocyte cryopreservation cycles before chemotherapy, when ovarian suppression is planned? Summary answer: The flare-up effect of long-acting GnRHa is able to induce the final oocytes' maturation and subsequently suppress ovarian function for chemotherapy What is known already: When both oocyte cryopreservation and gonadal suppression during chemotherapy with long-acting GnRHa are accepted by the patient for fertility preservation (FP), the first injection of GnRHa is administered few days after oocyte retrieval in order to start oncological therapies as soon as possible. Some cases of ovarian hyperstimulation (OHSS) have been described in this setting, as a consequence of the initial flare-up effect on recently stimulated ovaries. The subsequent risks (including a possible delay in the start of chemotherapy) may discourage physicians from proposing gonadal suppression in combination with oocyte cryopreservation, denying women a FP opportunity with proven efficacy. Study design, size, duration: Prospectively collected data from 75 oncological patients who underwent ovarian stimulation for oocyte cryopreservation from 2016 to 2021 were evaluated. From 2020 all patients for whom ovarian suppression after cryopreservation was planned were offered long-acting GnRHa trigger. All other patients were enrolled as controls, stratified for triggering method used (highly purified Chorionic Gonadotrophin 10000 UI or short acting GnRHa 0.2 mg). Participants/materials, setting, methods: All the ovarian stimulation cycles for oocyte cryopreservation in oncological patients before chemotherapy were performed in a single tertiary level public fertility centre. Cycle outcomes were evaluated accordingly to the trigger method. Maturation rate was defined as number of cryopreserved mature oocytes/total number of oocytes retrieved. Results were compared by Mann-Whitney U test or Chi-Square test, as appropriate. When the long-acting GnRHa was used for triggering, luteal phase hormones were assessed. Main results and the role of chance: After controlled ovarian stimulation (COS) with standard or random start antagonist protocol, 13 women received the long-acting GnRHa trigger (Triptorelin 3.75 mg. Group A) 36 hours before oocyte retrieval, 37 women received highly purified Chorionic Gonadotrophin 10000 UI (Group B) and 25 women the short-acting GnRHa (Triptorelin 0.2 mg. Group C). The groups were comparable in terms of demographic and clinical parameters. Median number of mature cryopreserved oocytes in group A was 11 (range 7-18) with a maturation rate of 80% (68-100), 9 (0-24) with a maturation rate of 78% (43-100) in group B, and 12 (0-34), 79% (50-100) in group C (no statistically significative difference). There was no case of OHSS in Group A. One patient in group B and one in group C developed OHSS after administration of long-acting GnRH in the luteal phase after COS (five days after oocytes retrieval). Five days after oocyte retrieval (7 days after trigger), serum FSH median level in group A was 1.29 mUI/ml (0.48-2.50) and LH median level was 1.04 mUI/ml (0.26-2.46). Limitations, reasons for caution: We are aware that our data should be confirmed by more robust randomized studies and higher numbers. Wider implications of the findings: We report for the first time the efficacy of long-acting GnRHa in obtaining mature oocytes and in guaranteeing complete suppression by chemotherapy initiation. The feasibility of this strategy is an important step in reducing the risk of OHSS, giving the opportunity to combine oocyte cryopreservation and ovarian suppression during chemotherapy. Trial registration number: not applicable